On the stability of the electronic system in transition metal dichalcogenides. (7th April 2016) - Faraggi, M N; Zubizarreta, X; Arnau, A; Silkin, V M
Abstract: Based on first-principles calculations, we prove that the origin of charge–density wave formation in metallic layered transition metal dichalcogenides (TMDC) is not due to an electronic effect, like the Fermi surface (FS) nesting, as it had been proposed. In particular, we consider NbSe2, NbS2, TaSe2, and TaS2 as representative examples of 2H-TMDC polytypes. Our main result consists that explicit inclusion of the matrix elements in first-principles calculations of the electron susceptibility χ 0 removes, due to strong momentum dependence of the matrix elements, almost all the information about the FS topologies in the resulting χ 0 . This finding strongly supports an interpretation in which the momentum dependence of the electron–phonon interaction is the only reason why the phenomenon of charge–density waves appears in this class of materials.